Dosing anticancer drugs in infants: Current approach and recommendations from the Children's Oncology Group's Chemotherapy Standardization Task Force. Issue 11 (16th May 2017) - Balis, Frank M.; Womer, Richard B.; Berg, Stacey; Winick, Naomi; Adamson, Peter C.; Fox, Elizabeth; ,
Abstract: An analysis of dose modifications for infants in 29 Children's Oncology Group protocols across 10 cancer types revealed 11 sets of criteria defining the infant population using age, weight, body surface area (BSA), or a combination of these parameters and eight dose modification methods. A new method of dosing anticancer drugs in infants was developed based on the rationale that prior modifications were implemented to reduce toxicity, which is not cancer‐specific. The new method uses BSA dose banding in dosing tables for infants and children with a BSA <0.6 m 2 and gradually transitions from body weight based to BSA‐based dosing.